2019
DOI: 10.1038/s41598-019-41865-z
|View full text |Cite
|
Sign up to set email alerts
|

Aescin-Cholesterol Complexes in DMPC Model Membranes: A DSC and Temperature-Dependent Scattering Study

Abstract: The saponin aescin, a mixture of triterpenoid saponins, is obtained from the seeds of the horse chestnut tree Aesculus hippocastanum . The β -form employed in this study is haemolytically active. The haemolytic activity results from the ability of aescin to form strong complexes with cholesterol in the red blood cell membrane. In this study, we provide a structural analysis on the complex formation of aescin and cholesterol when embedded in a phospholipid model mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 67 publications
4
35
0
Order By: Relevance
“…They found that the most prominent effect of β-aescin in the subphase occurs on cholesterol-containing monolayers confirming the strong affinity of β-aescin and cholesterol molecules. These results are in concordance with the effects of β-aescin on DMPC bilayers in the presence of cholesterol as discussed previously [55] (Section 6).…”
Section: Interaction Of β-Aescin With Langmuir Monolayers From Langmusupporting
confidence: 92%
See 2 more Smart Citations
“…They found that the most prominent effect of β-aescin in the subphase occurs on cholesterol-containing monolayers confirming the strong affinity of β-aescin and cholesterol molecules. These results are in concordance with the effects of β-aescin on DMPC bilayers in the presence of cholesterol as discussed previously [55] (Section 6).…”
Section: Interaction Of β-Aescin With Langmuir Monolayers From Langmusupporting
confidence: 92%
“…The effect of cholesterol addition on the structural parameters of β-aescin-containing phospholipid bilayers composed of DMPC was investigated by Sreij et al [55]. In this work, the cholesterol contents studied were 1, 5, and 10 mol% and the β-aescin contents ranged from 0 to 6 mol% with respect to the amount of DMPC in solution.…”
Section: Synergies Of β-Aescin Cholesterol and Drug Moleculesmentioning
confidence: 89%
See 1 more Smart Citation
“…In lipidic environment consisting of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC, Figure 1b, main phase transition temperature T m (DMPC) = 23.6 • C [30]), self-assembled and thermodynamically stable structures form, which depend on β-aescin concentration and lipid-to-saponin ratio [9]. Depending on β-ascin concentration phase segregation into saponin-rich and saponin-poor regions occurs, as proven by differential scanning calorimetry (DSC) [30][31][32]. Far below cmc(β-aescin), stable unilamellar vesicles are obtained by extrusion [33,34].…”
Section: Introductionmentioning
confidence: 97%
“…The phase behaviour of the β-aescin-DMPC mixtures can be modified through the addition of additive molecules, such as the steroid cholesterol ( Figure 1c) [32] or the NSAID ibuprofen ( Figure 1d) [31]. Cholesterol is one major compound in mammalian cells and its concentration can be as high as 50% in lipid bilayers [39].…”
Section: Introductionmentioning
confidence: 99%